Sustentabilidade: Desenvolvimento, Indicadores e Políticas públicas de planejamento para cidade de Cascavel – PR - Jorge Filho, Heitor Othelo (2023)
One of the relevant topics under discussion in academia and government is the issue of sustainability in municipalities and countries, justified by the increase in environmental, social and economic problems. This work aims to analyze, through indicators, the environmental, social and economic sustainability of the municipality of Cascavel, Paraná, in relation to the state capital, Curitiba, internationally recognized for its innovative urban planning. To this end, relevant sustainability criteria were established for the comparison between the two cities, including energy efficiency, waste management, urban mobility, urban green areas, land use and public policies. Specific data and documents were collected to be analyzed and compared quantitatively and qualitatively with the selected criteria. For energy efficiency, it was observed that Cascavel has a higher energy consumption per inhabitant compared to Curitiba. For organic waste, it was observed that Curitiba generated a greater amount per inhabitant than Cascavel. For public transport at a higher proportion of inhabitants per bus in Cascavel than Curitiba. For bicycle lanes, Curitiba has the highest density per inhabitant. For green areas, Curitiba has a higher proportion than Cascavel in terms of urbanized area, but per inhabitant Cascavel has a larger green area compared to Curitiba. For afforestation, both cities are concerned with this theme, but Curitiba is more wooded and has a more structured urban planning in relation to the preservation of green areas. For land use and occupation, both cities face challenges in terms of urban development, but Curitiba already has a long history of successful policies in this area. For public policies, both cities have programs that aim to promote sustainable practices and environmental awareness, Curitiba internationally recognized and Cascavel initiating and advancing in the promotion of urban sustainability. Both cities are committed to the issue, although at different stages of implementation and consolidation, Cascavel is in the process of development and seeks to expand its actions and Curitiba has already consolidated a management model and public policies that are internationally recognized.